Validation of the self-regulation of learning instrument for undergraduates - López-Angulo, Yaranay; Sáez-Delgado, Fabiola; Gaeta, Martha Leticia; Mella-Norambuena, Javier; González-Robaina, Yaynel; Muñoz-Inostroza, Karla (Frontiers in Education, 2024)
IntroductionSelf-regulation of learning is an essential variable in university students’ educational process and integral development, especially in the first semesters. Given its relevance, significant, valid, and reliable instruments are required for its measurement. Therefore, this study aimed to determine the psychometric properties of the SRLI-U scale that assesses Self-Regulation of Learning in Undergraduates.MethodsAn instrumental design was used, and the questionnaire was administered to 348 Chilean first-year university students (60.1% female) aged between 18 and 21 years (M = 18.85; SD = 0.773).ResultsAdequate adjustment indexes of the second order model were evidenced considering three dimensions theoretically coherent with Zimmerman’s model (1) Learning Disposition, Ω = 0.861, (2) Learning Performance, Ω = 0.842, and (3) Learning Self-evaluation, Ω = 0.887; and a general factor Ω = 0.936.ConclusionIt is a valid and reliable instrument for evaluating levels of self-regulation in Chilean university students.DiscussionThe SRLI-U constitutes a valuable tool for educational practice because it allows for evaluating, monitoring, and intervening the self-regulation of learning levels. Theoretical and practical implications are discussed, as well as the study’s limitations.